To develop formula for discharge through sluice gates in reservoirs - Lim, Siow Yong. (2011)
This report presents the results of investigation on the coefficient of discharge and channel delivery characteristics for the sluice gate structures at 5 reservoirs in Singapore; i.e., Jurong Lake, Kranji, Lower Seletar, Pandan and Poyan. Based on the available prototype drawings provided by PUB, the dimensions of the gates were extracted and model gates were constructed. The 5 sluice gates can be grouped in the following types and shapes; 1) Type A: Plain rectangular sluice gate - Jurong Lake. 2) Type B: Beveled rectangular sluice gate - Sungei Pandan and Sungei Seletar Reservoirs. 3) Type C: Combined sluice-flap gate - Kranji and Poyan Reservoirs. All the gates have sharp-edged at the point where water exits from the gate. Based on the extensive experimental data collected from the model study, the coefficients of discharge, Cd for estimating the discharge under free and submerged underflow conditions for the 5 sluice gates have been established. The weir coefficient, Cw for overflow through the sluice-flap gate of the Kranji reservoir has been obtained. These coefficients should be used with the discharge formulas (Equations 3.4 and 3.5) to calculate the volume of water discharge through the gates. A 1:50 scale model of the Kranji reservoir was fabricated to study the channel delivery characteristics when the gates are completely opened. A general formula (Equation 4.12) has been proposed to calculate the discharge through the gated waterways and it is applicable to various degree of channel constriction, i.e., whether one-, two- or threegates operation conditions.